An artificial prostate tissue induction composite material and preparation method thereof
By using prostate matrix made of peptide-metal composite polyether etherketone fibers in artificial prostate implant materials and coated with cytokine coating, the problems of insufficient mechanical strength and imperfect corrosion resistance in the biological environment are solved, achieving higher compatibility and nerve growth promotion effects.
Patent Information
- Application Number
- CN202411634423.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing artificial prostate implant materials have problems such as insufficient mechanical strength, impermissibility, and possible inflammatory response in the biological environment, making it difficult to maintain the normal functions of the urethra and urinary system in a long-term and stable manner.
Artificial prostate tissue-induced composite material, which includes a prostate matrix made of peptide-metal composite polyether etherketone fibers, DMAEMA-salt and methyl methacrylate, and is coated with a cytokine coating containing neuronal trophic factors on its surface.
It improves the compatibility of artificial prostate and human tissues, reduces the risk of inflammatory response, promotes nerve growth near the prostate, improves the mechanical properties and corrosion resistance of the material, and extends the service life of the material.
Smart Images

Figure CN119139546B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of implant materials, and specifically refers to an artificial prostate tissue induction composite material and a preparation method thereof. Background Art
[0002] Artificial prostate implant material is a medical device used to treat prostate-related diseases or perform prostate replacement surgery. Its use is usually related to prostate cancer, prostate hyperplasia or other prostate diseases. Common artificial prostate implant materials: prostate stents, which use implants to support or fix prostate tissue, are usually used to treat prostate hyperplasia or other structural problems; prostate substitutes, in some extreme cases, such as after prostatectomy, artificial prostate substitutes may be used to maintain the normal function of the urethra and urinary system. The biological materials of artificial prostate are mainly used for prostate replacement, support or treatment of related diseases, and are required to have good biocompatibility, mechanical strength and long-term stability. Commonly used biomaterials include the following categories: polytetrafluoroethylene (PTFE): has excellent chemical stability and biocompatibility, and is often used to make stents or other implants; polyethylene (PE): has high strength and wear resistance, and is widely used in medical implants, especially for support devices or wrapping materials; polylactic acid (PLA) and polyglycolic acid (PGA): biodegradable synthetic polymers, suitable for short-term implants, used for temporary support structures, and can be gradually absorbed by the body after implantation; silicone: due to its elasticity and biocompatibility, silicone is often used to make medical implants, such as devices used to support or replace part of the function of the prostate; a single biomaterial has limited flexibility and cannot be used in environments with high stress. It cannot be degraded in a biological environment. Long-term implantation may cause an inflammatory response, or the degradation process may cause a local acidic environment and stimulate surrounding tissues. Different biomaterials have their own unique advantages and limitations. In practical applications, it is usually necessary to make a reasonable choice based on clinical needs, and sometimes composite materials or coating technologies are used to optimize the performance of implants. Summary of the invention
[0003] In view of the above situation, in order to achieve the above purpose, the technical solution adopted by the present invention is as follows: The present invention proposes an artificial prostate tissue induction composite material, the composite material comprising an artificial prostate matrix and a cytokine coating:
[0004] Preferably, the artificial prostate matrix is obtained by curing the prostate matrix material, and the raw materials for preparing the artificial prostate matrix material include the following components in parts by weight: 5-10 parts of peptide-metal composite polyetheretherketone fiber, 12-15 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (DMAEMA-salt), and 20-25 parts of methyl methacrylate;
[0005] Preferably, the cytokine coating is formed by photocuring a cytokine coating precursor solution, and the raw materials for preparing the cytokine coating precursor solution include the following components in parts by weight: 5-8 parts of aldehyded chitosan powder, 14-18 parts of methacrylic anhydride, 3-5 parts of collagen powder, 0.8-1 part of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), and 5-6 parts of BDNF solution;
[0006] Preferably, the artificial prostate tissue induction composite material further comprises a signal acquisition module, a signal control module and a treatment module;
[0007] Preferably, the signal acquisition module collects the bladder and urethra pressure status, urine outflow and overflow status, and sends the data to the signal control module; the signal control module controls the treatment module to perform continuous discharge stimulation to adjust the bladder and urethra sensation and relieve the situation of frequent urination and urinary incontinence;
[0008] The present invention also provides a method for preparing an artificial prostate tissue induction composite material, which specifically comprises the following steps:
[0009] S1. Place the peptide-metal composite polyetheretherketone fiber in an ethanol solution, stir at a speed of 200-250 rpm, and fully disperse for 1-2 hours, then add DMAEMA-salt and methyl methacrylate to the reaction system, continue stirring and reacting for 2-3 hours, and then perform vacuum distillation to remove ethanol and deionized water to obtain an artificial prostate matrix solution;
[0010] S2, adding the artificial prostate matrix solution prepared in step S1 to the sodium persulfate solution, adjusting the pH to 8.5, and after mixing evenly, transferring to the prostate matrix mold, raising the reaction temperature to 40-50° C., and curing for 3-5 hours. After curing, demoulding, washing with deionized water, and vacuum drying to obtain an artificial prostate matrix;
[0011] S3, applying the cytokine coating precursor solution to the inner surface and outer surface of the artificial prostate precursor prepared in step S2, irradiating under blue-violet light for 30-60 seconds, and after the cytokine coating is cured, obtaining an artificial prostate tissue induction composite material;
[0012] Preferably, in step S1, the mass concentration of the peptide-metal composite polyetheretherketone fiber in the ethanol solution is 10-25 g / L;
[0013] Preferably, in step S2, the mass fraction of sodium persulfate in the sodium persulfate solution is 10%-20%, and the added volume of the sodium persulfate solution is 0.5%-1% of the volume of the artificial prostate matrix solution;
[0014] Preferably, the preparation method of the peptide-metal composite polyetheretherketone fiber specifically comprises the following steps:
[0015] T1, placing the polyetheretherketone fiber in a beaker, and washing it in an ultrasonic cleaning machine with acetone, anhydrous ethanol and deionized water in turn, the power of the ultrasonic cleaning machine is 500W, and the cleaning time is 30-60min, to remove impurities on the surface of the polyetheretherketone fiber, and after drying, obtain the pretreated polyetheretherketone fiber;
[0016] T2, soaking the pretreated polyetheretherketone fiber prepared in step T1 in concentrated sulfuric acid, performing ultrasonic treatment at a power of 400-600 W for 3-5 min, filtering, washing the solid with acetone and deionized water in turn, and drying to obtain sulfonated polyetheretherketone fiber;
[0017] T3, placing the sulfonated polyetheretherketone fiber prepared in step T2 in dichloromethane, adding aluminum chloride to mix, slowly adding succinic anhydride / dichloromethane solution, introducing nitrogen into the reaction system, raising the temperature to 40-45° C. under a nitrogen atmosphere, stirring at a speed of 150 rpm, reflux reaction for 4-6 hours, cooling the reaction system to room temperature, ultrasonically cleaning with sodium hydroxide solution, hydrochloric acid solution, deionized water and acetone at a power of 500 W, and drying to obtain modified polyetheretherketone fiber;
[0018] Preferably, in step T3, the mass concentration of the sulfonated polyetheretherketone fiber in dichloromethane is 25-50 g / L;
[0019] Preferably, in step T3, the mass concentration of succinic anhydride in dichloromethane is 0.065-0.1 g / mL, and the mass ratio between the sulfonated polyetheretherketone fiber and succinic anhydride is 2:1.5-2;
[0020] Preferably, in step T3, the mass ratio between the sulfonated polyetheretherketone fiber and anhydrous aluminum chloride is 1:1-1.2;
[0021] T4, dispersing the modified polyetheretherketone fiber prepared in step T3 in DMF, adding zinc chloride and mixing evenly, adding dopamine solution, stirring at a speed of 300-3500 rpm, adding p-toluenesulfonic acid, raising the reaction temperature to 90-100°C, stirring and reacting for 4-6 hours, removing the solvent by reduced pressure distillation, preparing a Tris buffer solution with a pH of 8.5-9.0, adding it to the reaction system, placing it at 37°C, stirring and reacting at a speed of 500-600 rpm for 20-28 hours, filtering, washing the precipitate with deionized water, anhydrous ethanol and acetone, and vacuum drying to obtain polydopamine-modified polyetheretherketone fiber;
[0022] Preferably, in step T4, the mass concentration of the modified polyetheretherketone fiber in DMF is 10-15 g / L;
[0023] Preferably, in step T4, the added mass of zinc chloride is 10%-20% of the mass of the modified polyetheretherketone fiber;
[0024] Preferably, in step T4, the dopamine solution is dopamine in an ethanol aqueous solution (V 乙醇 :V 水 =1:3), the mass concentration of dopamine in the ethanol aqueous solution is 40-60g / L; the mass ratio between the dopamine and the modified polyetheretherketone fiber is 1:0.7-0.9;
[0025] Preferably, in step T4, the added mass of the p-toluenesulfonic acid is 1%-2% of the mass of the modified polyetheretherketone fiber;
[0026] Preferably, in step T4, the volume ratio of the added volume of the Tris buffer solution to the volume of the DMF solvent is 1-1.5:1;
[0027] T5. Dissolve L-histidine in tetrahydrofuran, add triphosgene under nitrogen atmosphere, raise the reaction temperature to 50-60°C, stir and react for 1-2h, wait for the reaction system to cool, add n-hexane for sedimentation, filter, take the precipitate, recrystallize with ethyl acetate, and dry to obtain histidine-NCA;
[0028] Preferably, in step T5, the mass concentration of L-histidine in tetrahydrofuran is 60-80 g / L;
[0029] Preferably, in step T5, the mass ratio between L-histidine and triphosgene is 1:1.2-1.5;
[0030] T6, placing the polydopamine-modified polyetheretherketone fiber prepared in step T4 in dichloromethane, adding the histidine-NCA prepared in step T5, placing it in an argon atmosphere, stirring at a speed of 400-600 rpm for reaction, after 24-36 hours, filtering to remove the solvent, washing with DMF and dichloromethane, and vacuum drying to obtain a polypeptide composite polyetheretherketone fiber;
[0031] Preferably, in step T6, the mass concentration of the polydopamine-modified polyetheretherketone fiber in dichloromethane is 40-50 g / L;
[0032] Preferably, in step T6, the mass ratio between the polydopamine-modified polyetheretherketone fiber and histidine-NCA is 1:3-4;
[0033] T7, dispersing the polypeptide composite polyetheretherketone fiber prepared in step T6 in anhydrous ethanol, adding zinc chloride, stirring at 400-500 rpm at room temperature, reacting for 4-6 hours, dialyzing with Tris buffer using a 3500Da dialysis bag for 24 hours, and freeze-drying to obtain the peptide-metal composite polyetheretherketone fiber;
[0034] Preferably, in step T7, the mass concentration of the polypeptide composite polyetheretherketone fiber in anhydrous ethanol is 10-15 g / L;
[0035] Preferably, in step T7, the added mass of zinc chloride is 15%-20% of the mass of the polypeptide composite polyetheretherketone fiber;
[0036] Preferably, the method for preparing the cytokine coating precursor solution specifically comprises the following steps:
[0037] K1. Place chitosan in deionized water, adjust the pH to 5.5-6.5 to completely dissolve the chitosan, add sodium periodate, mix well, place at room temperature, react in the dark for 6-8 hours, add ascorbic acid to terminate the reaction until the color of the reaction system no longer changes, and after the reaction is completed, freeze-dry to obtain aldehyded chitosan;
[0038] Preferably, in step K1, the mass concentration of chitosan in deionized water is 15-25 g / L;
[0039] Preferably, in step K1, the mass ratio between chitosan and sodium periodate is 10:8-9;
[0040] K2, dispersing the aldehyde-modified chitosan prepared in step K1 in DMF solvent, adding hydrogen peroxide, stirring at 150 rpm until the aldehyde-modified chitosan is completely dissolved, adding methacrylic anhydride, adjusting the pH of the reaction system to 8-9, placing in an ice-water bath environment, continuing to stir and react for 12 hours, placing in a dialysis bag after the reaction is completed, dialyzing with deionized water for 2 days, and freeze-drying to obtain modified chitosan powder;
[0041] Preferably, in step K2, the mass concentration of the aldehyde-modified chitosan in the DMF solvent is 40-60 g / L;
[0042] Preferably, in step K2, the volume ratio of the added volume of hydrogen peroxide to the volume of the DMF solvent is 1-1.5:1;
[0043] K3, dissolving collagen in a NaCl aqueous solution, adding the modified chitosan powder prepared in step K2, stirring at a speed of 200 rpm, adding 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, mixing evenly at 4°C, adding BDNF solution, and continuing stirring for 2-3 hours to obtain a cytokine coating precursor solution;
[0044] Preferably, in step K3, the mass fraction of the NaCl aqueous solution is 1%-1.2%; the mass concentration of the collagen in the NaCl aqueous solution is 20-25 g / L;
[0045] Preferably, in step K3, the BDNF solution is a solution of BDNF dissolved in deionized water, with a mass concentration of 10 μg / mL.
[0046] The beneficial effects achieved by the present invention are as follows:
[0047] The invention provides an artificial prostate tissue induction composite material and a preparation method thereof. The invention prepares an artificial prostate matrix and coats a coating containing a nerve cell trophic factor on the surface of the artificial prostate matrix, thereby improving the compatibility of the artificial prostate with human tissues and avoiding inflammatory reactions caused by the artificial prostate. Meanwhile, the release of the nerve cell trophic factor can promote nerve growth near the prostate. The artificial prostate matrix prepared by the invention uses acrylic resin as the main matrix material and is filled with peptide-metal composite modified polyetheretherketone fiber, thereby effectively improving the mechanical properties and corrosion resistance of the artificial prostate matrix material, making the elastic properties of the artificial prostate matrix material better, reducing the foreign body sensation in the human body, and the modified polyetheretherketone fiber can maintain structural strength and avoid deformation of the artificial prostate matrix. In the invention, the modified polyetheretherketone fiber is modified by carboxylation to increase the reaction ability with dopamine hydroxyl groups and increase the adhesion ability of polydopamine on the surface of the polyetheretherketone fiber. Due to the formation of the polydopamine coating layer , amino groups are introduced into the surface of polyetheretherketone fiber, and peptide complexes are formed through polymerization reaction of amino groups and histidine polypeptides. At the same time, the imidazole groups on the histidine can form a highly active surface structure with zinc element, which can have a significant effect on the mechanical strength and toughness of the artificial prostate matrix, and at the same time, it can overcome the rejection reaction between polyetheretherketone and the human body; in the present invention, DMAEMA-salt is used as one of the specific monomers of acrylic acid, and its molecular structure is amphiphilic and has cationic ammonium groups, which can improve the antibacterial properties of the artificial prostate matrix. It has an anionic sulfonic acid group at the end of the molecule, which can form an electrostatic adsorption effect with the cationic group in the chitosan in the coating solution, thereby improving the adhesion of the coating to the prostate matrix; the cytokine coating described in the present invention includes BDNF, which is a key nerve growth factor. After nerve damage or neurodegenerative diseases, BDNF can promote the regeneration and repair of damaged nerves and accelerate functional recovery. Through the sustained release of the coating, it can improve the repair and growth of nerve cells around the artificial prostate matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a SEM image of the microstructure of the artificial prostate matrix prepared in Example 1;
[0049] Figure 2 Schematic diagram of the structure of the artificial prostate tissue induction composite material prepared in Example 1; 1 is the artificial prostate matrix, 2 is the cytokine coating;
[0050] Figure 3 The mechanical properties of the prostate precursor substrates prepared in Examples 1-3 and Comparative Examples 1-3 are shown in FIG.
[0051] Figure 4The figure is a result diagram of the release performance of BDNF of the artificial prostate tissue-induced composite materials prepared in Example 1 and Comparative Examples 1-4;
[0052] Figure 5 This is a diagram showing the long-term sustained release effect of the artificial prostate tissue-induced composite material prepared in Example 1 and Comparative Examples 1 and 3 of the present invention.
[0053] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0054] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0055] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0056] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.
[0057] Example 1
[0058] This embodiment provides an artificial prostate tissue induction composite material, including an artificial prostate matrix and a cytokine coating;
[0059] The artificial prostate tissue induction composite material also includes a signal acquisition module, a signal control module and a treatment module;
[0060] The signal acquisition module collects the bladder and urethra pressure status, urine outflow and overflow status, and sends the data to the signal control module; the signal control module controls the treatment module to perform continuous discharge stimulation to adjust the bladder and urethra sensation and relieve the condition of frequent urination and urinary incontinence;
[0061] The artificial prostate matrix is obtained by curing the prostate matrix material. The raw materials for preparing the artificial prostate matrix material include the following components in parts by weight: 5 parts of peptide-metal composite polyetheretherketone fiber, 12 parts of DMAEMA-salt, and 20 parts of methyl methacrylate;
[0062] The preparation method of peptide-metal composite polyetheretherketone fiber specifically comprises the following steps:
[0063] T1, placing the polyetheretherketone fiber in a beaker, and washing it in an ultrasonic cleaning machine with acetone, anhydrous ethanol and deionized water in turn, the power of the ultrasonic cleaning machine is 500W, the cleaning time is 30min, the impurities on the surface of the polyetheretherketone fiber are removed, and after drying, the pretreated polyetheretherketone fiber is obtained;
[0064] T2, soaking the pretreated polyetheretherketone fiber prepared in step T1 in concentrated sulfuric acid, performing ultrasonic treatment at a power of 400 W for 3 min, filtering, washing the solid with acetone and deionized water in turn, and drying to obtain the sulfonated polyetheretherketone fiber;
[0065] T3, accurately weigh 2g of sulfonated polyetheretherketone fiber and place it in 80mL of dichloromethane, accurately weigh 2g of anhydrous aluminum chloride and place it in the reaction system, mix well, accurately weigh 1.5g of succinic anhydride and dissolve it in 20mL of dichloromethane, introduce nitrogen into the reaction system, slowly drop succinic anhydride / dichloromethane solution at a rate of 1mL / min, raise the temperature to 45°C under nitrogen atmosphere, stir at a speed of 150rpm, reflux for 4h, after the reaction is completed, wait for the reaction system to cool to room temperature, and use 5wt% sodium hydroxide solution, 5wt% hydrochloric acid solution, deionized water and acetone to ultrasonically clean at 500W power in sequence, and vacuum dry at 40°C for 3h to obtain modified polyetheretherketone fiber;
[0066] T4, accurately weigh 1 g of the modified polyetheretherketone fiber prepared in step T3 and disperse it in 100 mL of DMF, accurately weigh 0.1 g of zinc chloride and add it to the reaction system, stir to fully dissolve, accurately weigh 0.8 g of dopamine hydrochloride and dissolve it in 20 mL of ethanol aqueous solution (V 乙醇 :V 水 =1:3) was added to the reaction system, stirred at 300 rpm, 0.01 g of p-toluenesulfonic acid was added, the reaction temperature was raised to 100°C, and the reaction was continued with stirring for 5 hours. The solvent was removed by distillation under reduced pressure, and a Tris buffer solution with a pH of 8.5 was prepared. 100 mL of the solution was added to the reaction system, and the solution was placed at 37°C, stirred at 600 rpn for 24 hours, and filtered. The precipitate was washed three times with deionized water, anhydrous ethanol and acetone in sequence, and dried under vacuum at 40°C for 12 hours to obtain polydopamine-modified polyetheretherketone fiber.
[0067] T5. Accurately weigh 15 g of L-histidine and add it to a flask. Add 250 mL of tetrahydrofuran, evacuate until no bubbles are generated, continue to introduce flowing nitrogen into the reaction system, stir at 150 rpm, add 9 g of triphosgene, mix well, raise the reaction temperature to 55 ° C, continue to stir and react for 1 hour, add 9 g of triphosgene, continue to stir and react for 1 hour, stop adding after the reaction solution gradually becomes clear, concentrate the reaction system to 20% of the original volume, add pre-cooled n-hexane to the reaction system for sedimentation, filter, collect the precipitate, dissolve it in 50 mL of ethyl acetate for recrystallization, place it in a nitrogen environment, dry it, remove excess solvent, and obtain histidine-NCA;
[0068] T6, 0.5 g of the polydopamine-modified polyetheretherketone fiber prepared in step T4 was placed in a beaker, 10 mL of dichloromethane was added for thorough mixing, 1.5 g of histidine-NCA prepared in step T5 was added, the reaction system was evacuated, argon was introduced, and the reaction was stirred at 400 rpm for 36 hours under an argon atmosphere, and then the dichloromethane was removed by suction filtration, and the fiber was washed repeatedly with DMF and dichloromethane three times in sequence, and then placed at 40° C. and vacuum dried for 12 hours to obtain a polypeptide composite polyetheretherketone fiber;
[0069] T7, dispersing 0.1 g of the polypeptide composite polyetheretherketone fiber prepared in step T6 in 10 mL of anhydrous ethanol, accurately weighing 1 g of zinc chloride and dissolving it in 100 mL of deionized water, taking 2 mL and adding it to the reaction system, stirring at 500 rpm at room temperature, reacting for 5 h, transferring the reaction system to a 3500 Da dialysis bag, dialyzing with a Tris solution with a pH of 7.6, and freeze-drying after 24 h to obtain the peptide-metal composite polyetheretherketone fiber;
[0070] The cytokine coating is formed by light curing a cytokine coating precursor solution, and the raw materials for preparing the cytokine coating precursor solution include the following components in parts by weight: 8 parts of aldehyded chitosan powder, 14 parts of methacrylic anhydride, 5 parts of collagen powder, 0.8 parts of TPO, and 6 parts of BDNF solution;
[0071] The method for preparing a cytokine coating precursor solution specifically comprises the following steps:
[0072] K1. Accurately weigh 5 g of chitosan and disperse it in 200 mL of deionized water. Adjust the pH of the reaction system to 5.5 to completely dissolve the chitosan. Add 4 g of sodium periodate and mix well. Place the mixture at room temperature and react in the dark for 8 h. Add ascorbic acid to terminate the reaction until the color of the reaction system no longer changes. After the reaction is completed, dialyze with deionized water for 2 d using a dialysis bag with a cutoff of 3.5 kDa, and freeze-dry to obtain aldehyded chitosan.
[0073] K2, 0.8 g of the aldehyded chitosan prepared in step K1 was dispersed in 20 mL of DMF solvent, 20 mL of 3 wt% hydrogen peroxide solution was added, and the mixture was stirred at 150 rpm until the aldehyded chitosan was completely dissolved, 1.4 mL of methacrylic anhydride was added, the pH of the reaction system was adjusted to 8, and the mixture was placed in an ice-water bath environment, and the stirring reaction was continued for 12 h. After the reaction was completed, the mixture was placed in a dialysis bag with a cutoff of 3.5 kDa, and dialyzed with deionized water for 2 d. After freeze-drying, modified chitosan powder was obtained;
[0074] K3, dissolving 0.5 g collagen in 20 mL of 1 wt% NaCl aqueous solution, adding the modified chitosan powder prepared in step K2, stirring at 200 rpm, adding 0.08 g TPO, mixing evenly at 4 ° C, adding 0.6 mL of 10 μg / mL BDNF solution, and continuing stirring for 2 h to obtain a cytokine coating precursor solution;
[0075] This embodiment also provides an artificial prostate tissue induction composite material, which specifically includes the following steps:
[0076] S1. Place 2 g of peptide-metal composite polyetheretherketone fiber in 30 vol% 100 mL ethanol solution, perform ultrasonic treatment at 500 W power for 20 min to fully infiltrate the peptide-metal composite polyetheretherketone fiber in the ethanol solution, stir at 200 rpm, react for 2 h, add 4.8 g of DMAEMA-salt and 8.5 mL of methyl methacrylate to the reaction system, continue stirring and reacting for 2 h, and perform reduced pressure distillation to remove ethanol and deionized water to obtain an artificial prostate matrix solution;
[0077] S2, taking 20mL of the artificial prostate matrix solution, adding 0.2mL of 10wt% sodium persulfate solution, adjusting the pH to 8.5, mixing evenly, transferring to the prostate matrix mold, raising the reaction temperature to 40°C, and curing for 5 hours, demolding after curing, washing with deionized water, and vacuum drying to obtain an artificial prostate matrix;
[0078] The surface morphology of the samples was observed using a scanning electron microscope (SEM, XL30 FEG, Philips). Figure 1 This is a SEM image of the microstructure of the artificial prostate matrix prepared in this example. As shown in the figure, the artificial prostate matrix is composed of a dense network structure.
[0079] S3. Apply the cytokine coating precursor solution to the inner and outer surfaces of the artificial prostate precursor prepared in step S2, and irradiate under blue-violet light for 30 seconds. After the cytokine coating is cured, an artificial prostate tissue induction composite material is obtained.
[0080] The structural schematic diagram of the artificial prostate tissue induction composite material prepared in this embodiment is shown in FIG. Figure 2 As shown, 1 is an artificial prostate matrix and 2 is a cytokine coating.
[0081] Example 2
[0082] This embodiment provides an artificial prostate tissue induction composite material, including an artificial prostate matrix and a cytokine coating;
[0083] The artificial prostate tissue induction composite material also includes a signal acquisition module, a signal control module and a treatment module;
[0084] The signal acquisition module collects the bladder and urethra pressure status, urine outflow and overflow status, and sends the data to the signal control module; the signal control module controls the treatment module to perform continuous discharge stimulation to adjust the bladder and urethra sensation and relieve the condition of frequent urination and urinary incontinence;
[0085] The artificial prostate matrix is obtained by curing the prostate matrix material. The raw materials for preparing the artificial prostate matrix material include the following components in parts by weight: 8 parts of peptide-metal composite polyetheretherketone fiber, 15 parts of DMAEMA-salt, and 22 parts of methyl methacrylate;
[0086] The preparation method of peptide-metal composite polyetheretherketone fiber specifically comprises the following steps:
[0087] T1, placing the polyetheretherketone fiber in a beaker, and washing it in an ultrasonic cleaning machine with acetone, anhydrous ethanol and deionized water in turn, the power of the ultrasonic cleaning machine is 500W, the cleaning time is 40min, the impurities on the surface of the polyetheretherketone fiber are removed, and after drying, the pretreated polyetheretherketone fiber is obtained;
[0088] T2, soaking the pretreated polyetheretherketone fiber prepared in step T1 in concentrated sulfuric acid, performing ultrasonic treatment at 600W power for 5 minutes, filtering, washing the solid with acetone and deionized water in turn, and drying to obtain sulfonated polyetheretherketone fiber;
[0089] T3, accurately weigh 3g of sulfonated polyetheretherketone fiber and place it in 90mL of dichloromethane, accurately weigh 4.8g of anhydrous aluminum chloride and place it in the reaction system, mix well, accurately weigh 4g of succinic anhydride and dissolve it in 60mL of dichloromethane, introduce nitrogen into the reaction system, slowly drop succinic anhydride / dichloromethane solution at a rate of 1mL / min, raise the temperature to 40°C under nitrogen atmosphere, stir at a speed of 150rpm, reflux for 6h, after the reaction is completed, wait for the reaction system to cool to room temperature, and use 5wt% sodium hydroxide solution, 5wt% hydrochloric acid solution, deionized water and acetone to ultrasonically clean at 500W power in sequence, and vacuum dry at 40°C for 3h to obtain modified polyetheretherketone fiber;
[0090] T4, accurately weigh 1.5 g of the modified polyetheretherketone fiber prepared in step T3 and disperse it in 100 mL of DMF, accurately weigh 0.3 g of zinc chloride and add it to the reaction system, stir to fully dissolve, accurately weigh 1.35 g of dopamine hydrochloride and dissolve it in 22.5 mL of ethanol aqueous solution (V 乙醇 :V 水 =1:3) was added to the reaction system, stirred at 350 rpm, 0.03 g of p-toluenesulfonic acid was added, the reaction temperature was raised to 80°C, and the reaction was continued with stirring for 6 hours. The solvent was removed by vacuum distillation to prepare a Tris buffer solution with a pH of 9.0, 150 mL of which was added to the reaction system, placed at 37°C, stirred at 500 rpn for 20 hours, filtered, and the precipitate was washed repeatedly three times with deionized water, anhydrous ethanol and acetone in sequence, and placed at 40°C for vacuum drying for 12 hours to obtain polydopamine-modified polyetheretherketone fiber;
[0091] T5. Accurately weigh 16 g of L-histidine and add it to a flask. Add 200 mL of tetrahydrofuran, evacuate until no bubbles are generated, continue to introduce flowing nitrogen into the reaction system, place it under stirring at 150 rpm, add 10 g of triphosgene, mix well, raise the reaction temperature to 50 ° C, continue to stir and react for 2 hours, add 14 g of triphosgene, continue to stir and react for 1 hour, stop adding after the reaction solution gradually becomes clear, concentrate the reaction system to 20% of the original volume, add pre-cooled n-hexane to the reaction system for sedimentation, filter, collect the precipitate, dissolve it in 50 mL of ethyl acetate for recrystallization, place it in a nitrogen environment, dry it, remove excess solvent, and obtain histidine-NCA;
[0092] T6, 0.4 g of the polydopamine-modified polyetheretherketone fiber prepared in step T4 was placed in a beaker, 10 mL of dichloromethane was added for thorough mixing, 1.6 g of histidine-NCA prepared in step T5 was added, the reaction system was evacuated, argon was introduced, and the reaction was stirred at 600 rpm for 24 h under an argon atmosphere, and then the dichloromethane was removed by suction filtration, and the fiber was washed repeatedly with DMF and dichloromethane three times in sequence, and then placed at 40° C. and vacuum dried for 12 h to obtain a polypeptide composite polyetheretherketone fiber;
[0093] T7, dispersing 0.2 g of the polypeptide composite polyetheretherketone fiber prepared in step T6 in 10 mL of anhydrous ethanol, accurately weighing 1 g of zinc chloride and dissolving it in 100 mL of deionized water, taking 3 mL and adding it to the reaction system, stirring at 600 rpm at room temperature, reacting for 4 h, transferring the reaction system to a 3500 Da dialysis bag, dialyzing with a Tris solution with a pH of 7.6, and freeze-drying after 24 h to obtain the peptide-metal composite polyetheretherketone fiber;
[0094] The cytokine coating is formed by light curing a cytokine coating precursor solution, and the raw materials for preparing the cytokine coating precursor solution include the following components in parts by weight: 6 parts of aldehyded chitosan powder, 18 parts of methacrylic anhydride, 3 parts of collagen powder, 1 part of TPO, and 5 parts of BDNF solution;
[0095] The method for preparing a cytokine coating precursor solution specifically comprises the following steps:
[0096] K1. Accurately weigh 3 g of chitosan and disperse it in 200 mL of deionized water. Adjust the pH of the reaction system to 6.5 to completely dissolve the chitosan. Add 2.7 g of sodium periodate and mix well. Place the mixture at room temperature and react in the dark for 6 h. Add ascorbic acid to terminate the reaction until the color of the reaction system no longer changes. After the reaction is completed, dialyze with deionized water for 2 d using a dialysis bag with a cutoff of 3.5 kDa and freeze-dry to obtain aldehyde-modified chitosan.
[0097] K2, 1.5 g of the aldehyded chitosan prepared in step K1 was dispersed in 25 mL of DMF solvent, 30 mL of 3 wt% hydrogen peroxide solution was added, and the mixture was stirred at 150 rpm until the aldehyded chitosan was completely dissolved, 4.5 mL of methacrylic anhydride was added, the pH of the reaction system was adjusted to 8.5, and the mixture was placed in an ice-water bath environment, and the stirring reaction was continued for 12 h. After the reaction was completed, the mixture was placed in a dialysis bag with a cutoff of 3.5 kDa, and dialyzed with deionized water for 2 d. After freeze-drying, modified chitosan powder was obtained;
[0098] K3, dissolving 0.75 g collagen in 30 mL of 1.2 wt% NaCl aqueous solution, adding the modified chitosan powder prepared in step K2, stirring at 200 rpm, adding 0.25 g TPO, mixing evenly at 4 ° C, adding 1.25 mL of 10 μg / mL BDNF solution, and continuing stirring for 3 h to obtain a cytokine coating precursor solution;
[0099] This embodiment also provides an artificial prostate tissue induction composite material, which specifically includes the following steps:
[0100] S1, placing 2g of peptide-metal composite polyetheretherketone fiber in 30vol% 100mL ethanol solution, ultrasonically treating at 500W power for 20min to fully infiltrate the peptide-metal composite polyetheretherketone fiber in the ethanol solution, adding 3.8g of DMAEMA-salt and 5.5mL of methyl methacrylate, continuing to stir and react for 2h, and then distilling under reduced pressure to remove ethanol and deionized water to obtain an artificial prostate matrix solution;
[0101] S2, taking 20mL of the artificial prostate matrix solution, adding 0.1mL of 15wt% sodium persulfate solution, adjusting the pH to 8.5, mixing evenly, transferring to the prostate matrix mold, raising the reaction temperature to 50°C, and curing for 3h, demoulding after curing, washing with deionized water, and vacuum drying to obtain an artificial prostate matrix;
[0102] S3. Apply the cytokine coating precursor solution to the inner and outer surfaces of the artificial prostate precursor prepared in step S2, and irradiate under blue-violet light for 45 seconds. After the cytokine coating is cured, an artificial prostate tissue induction composite material is obtained.
[0103] Experimental Example 3
[0104] This embodiment provides an artificial prostate tissue induction composite material, including an artificial prostate matrix and a cytokine coating;
[0105] The artificial prostate tissue induction composite material also includes a signal acquisition module, a signal control module and a treatment module;
[0106] The signal acquisition module collects the bladder and urethra pressure status, urine outflow and overflow status, and sends the data to the signal control module; the signal control module controls the treatment module to perform continuous discharge stimulation to adjust the bladder and urethra sensation and relieve the condition of frequent urination and urinary incontinence;
[0107] The artificial prostate matrix is obtained by curing the prostate matrix material. The raw materials for preparing the artificial prostate matrix material include the following components in parts by weight: 10 parts of peptide-metal composite polyetheretherketone fiber, 15 parts of DMAEMA-salt, and 25 parts of methyl methacrylate;
[0108] The preparation method of peptide-metal composite polyetheretherketone fiber specifically comprises the following steps:
[0109] T1, placing the polyetheretherketone fiber in a beaker, and washing it in an ultrasonic cleaning machine with acetone, anhydrous ethanol and deionized water in turn, the power of the ultrasonic cleaning machine is 500W, the cleaning time is 60min, the impurities on the surface of the polyetheretherketone fiber are removed, and after drying, the pretreated polyetheretherketone fiber is obtained;
[0110] T2, soaking the pretreated polyetheretherketone fiber prepared in step T1 in concentrated sulfuric acid, performing ultrasonic treatment at a power of 400 W for 3 min, filtering, washing the solid with acetone and deionized water in turn, and drying to obtain the sulfonated polyetheretherketone fiber;
[0111] T3. Accurately weigh 5 g of sulfonated polyetheretherketone fiber and place it in 100 mL of dichloromethane. Accurately weigh 5 g of anhydrous aluminum chloride and place it in the reaction system. After mixing evenly, accurately weigh 5 g of succinic anhydride and dissolve it in 50 mL of dichloromethane. Pass nitrogen into the reaction system, slowly drop the succinic anhydride / dichloromethane solution at a rate of 1 ml / min, raise the temperature to 40°C in a nitrogen atmosphere, stir at a speed of 150 rpm, and reflux for 5 hours. After the reaction is completed, cool the reaction system to room temperature, and use 5 wt% sodium hydroxide solution, 5 wt% hydrochloric acid solution, deionized water and acetone to ultrasonically clean it at 500 W in sequence. After vacuum drying at 40°C for 3 hours, obtain modified polyetheretherketone fiber;
[0112] T4, accurately weigh 2 g of the modified polyetheretherketone fiber prepared in step T3 and disperse it in 200 mL of DMF, accurately weigh 0.3 g of zinc chloride and add it to the reaction system, stir to fully dissolve, accurately weigh 1.4 g of dopamine hydrochloride and dissolve it in 28 mL of ethanol aqueous solution (V 乙醇 :V 水 =1:3) was added to the reaction system, stirred at 330 rpm, 0.03 g of p-toluenesulfonic acid was added, the reaction temperature was raised to 90°C, and the reaction was continued with stirring for 4 hours. The solvent was removed by distillation under reduced pressure, and a Tris buffer solution with a pH of 8.5 was prepared. 200 mL of the solution was added to the reaction system, and the solution was placed at 37°C. The solution was stirred at 550 rpn for 28 hours, and then filtered. The precipitate was washed three times with deionized water, anhydrous ethanol and acetone in sequence, and dried under vacuum at 40°C for 12 hours to obtain polydopamine-modified polyetheretherketone fiber.
[0113] T5. Accurately weigh 10 g L-histidine and add it to a flask, add 150 mL tetrahydrofuran, evacuate until no bubbles are generated, continue to introduce flowing nitrogen into the reaction system, place it under stirring at 150 rpm, add 7 g triphosgene, mix well, increase the reaction temperature to 60 ° C, continue to stir and react for 1.5 hours, add 7 g triphosgene, continue to stir and react for 1 hour, stop adding after the reaction solution gradually becomes clear, concentrate the reaction system to 20% of the original volume, add pre-cooled n-hexane to the reaction system for sedimentation, filter, collect the precipitate, dissolve it in 50 mL ethyl acetate for recrystallization, place it in a nitrogen environment, dry it, remove excess solvent, and obtain histidine-NCA;
[0114] T6, 0.9 g of the polydopamine-modified polyetheretherketone fiber prepared in step T4 was placed in a beaker, 20 mL of dichloromethane was added for thorough mixing, 3.2 g of histidine-NCA prepared in step T5 was added, the reaction system was evacuated, argon was introduced, and the reaction was stirred at 500 rpm for 30 h under an argon atmosphere, and then the dichloromethane was removed by suction filtration, and the fiber was washed repeatedly with DMF and dichloromethane three times in sequence, and then placed at 40° C. and vacuum dried for 12 h to obtain a polypeptide composite polyetheretherketone fiber;
[0115] T7, dispersing 0.1 g of the polypeptide composite polyetheretherketone fiber prepared in step T6 in 10 mL of anhydrous ethanol, accurately weighing 1 g of zinc chloride and dissolving it in 100 mL of deionized water, taking 20 mL and adding it to the reaction system, stirring at 400 rpm at room temperature, reacting for 6 hours, transferring the reaction system to a 3500Da dialysis bag, dialyzing it with a Tris solution with a pH of 7.6, and freeze-drying it after 24 hours to obtain the peptide-metal composite polyetheretherketone fiber;
[0116] The cytokine coating is formed by light curing a cytokine coating precursor solution, and the raw materials for preparing the cytokine coating precursor solution include the following components in parts by weight: 6 parts of aldehyded chitosan powder, 16 parts of methacrylic anhydride, 4 parts of collagen powder, 0.9 parts of TPO, and 5 parts of BDNF solution;
[0117] The method for preparing a cytokine coating precursor solution specifically comprises the following steps:
[0118] K1. Accurately weigh 4 g of chitosan and disperse it in 200 mL of deionized water. Adjust the pH of the reaction system to 6 to completely dissolve the chitosan. Add 3.5 g of sodium periodate and mix well. Place the mixture at room temperature and react in the dark for 7 h. Add ascorbic acid to terminate the reaction until the color of the reaction system no longer changes. After the reaction is completed, dialyze with deionized water for 2 d using a dialysis bag with a cutoff of 3.5 kDa and freeze-dry to obtain aldehyded chitosan.
[0119] K2, 1.5 g of the aldehyded chitosan prepared in step K1 was dispersed in 30 mL of DMF solvent, 20 mL of 3 wt% hydrogen peroxide solution was added, and the mixture was stirred at 150 rpm until the aldehyded chitosan was completely dissolved, 4 mL of methacrylic anhydride was added, the pH of the reaction system was adjusted to 8, and the mixture was placed in an ice-water bath environment, and the stirring reaction was continued for 12 h. After the reaction was completed, the mixture was placed in a dialysis bag with a cutoff of 3.5 kDa, and dialyzed with deionized water for 2 d. After freeze-drying, modified chitosan powder was obtained;
[0120] K3, dissolving 1 g of collagen in 50 mL of 1.1 wt% NaCl aqueous solution, adding the modified chitosan powder prepared in step K2, stirring at 200 rpm, adding 0.225 g of TPO, mixing evenly at 4 ° C, adding 1.25 mL of 10 μg / mL BDNF solution, and continuing stirring for 2.5 h to obtain a cytokine coating precursor solution;
[0121] This embodiment also provides an artificial prostate tissue induction composite material, which specifically includes the following steps:
[0122] S1. Place 5 g of peptide-metal composite polyetheretherketone fiber in 30 vol% 200 mL ethanol solution, perform ultrasonic treatment at 500 W power for 20 min to fully infiltrate the peptide-metal composite polyetheretherketone fiber in the ethanol solution, stir at 250 rpm, react for 1 h, add 7.5 g of DMAEMA-salt and 12.5 mL of methyl methacrylate to the reaction system, continue stirring and reacting for 3 h, and perform reduced pressure distillation to remove ethanol and deionized water to obtain an artificial prostate matrix solution;
[0123] S2, taking 20mL of the artificial prostate matrix solution, adding 0.1mL of 20wt% sodium persulfate solution, adjusting the pH to 8.5, mixing evenly, transferring to the prostate matrix mold, raising the reaction temperature to 45°C, and curing for 4 hours, demolding after curing, washing with deionized water, and vacuum drying to obtain an artificial prostate matrix;
[0124] S3. Apply the cytokine coating precursor solution to the inner and outer surfaces of the artificial prostate precursor prepared in step S2, and irradiate under blue-violet light for 60 seconds. After the cytokine coating is cured, an artificial prostate tissue induction composite material is obtained.
[0125] Comparative Example 1
[0126] This comparative example provides an artificial prostate composite material and a preparation method thereof, which differs from Example 1 only in that the raw materials for preparing the artificial prostate matrix material do not include peptide-metal composite polyetheretherketone fiber, which is replaced by polyetheretherketone fiber of the same mass fraction, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0127] Comparative Example 2
[0128] This comparative example provides an artificial prostate composite material and a preparation method thereof, which differs from Example 1 only in that DMAEMA salt is not included in the raw materials for preparing the artificial prostate matrix material, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0129] Comparative Example 3
[0130] This comparison provides an artificial prostate composite material and a preparation method thereof, which differs from Example 1 only in that the preparation method of the peptide-metal composite polyetheretherketone fiber does not include step T4, that is, the surface of the polyetheretherketone fiber is not coated with polydopamine, and is only a peptide-metal coated polyetheretherketone fiber, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0131] Comparative Example 4
[0132] This comparative example provides an artificial prostate composite material and a preparation method thereof, which differs from Example 1 only in that, in the preparation method of the cytokine coating precursor solution, chitosan is replaced by hyaluronic acid at the same mass ratio, and the remaining components, component contents and preparation methods are the same as those in Example 1.
[0133] Experimental Example 1
[0134] In this experimental example, the mechanical properties of the prostate precursor matrix prepared in Examples 1-3 and Comparative Examples 1-3 were measured. After the artificial prostate matrix solutions prepared in Examples and Comparative Examples 1-3 were solidified, artificial anterior lacrimal gland matrix samples with a size of 50×10×5 mm were made. The three-point bending method specified in ISO 14125 was used to place the samples on an AGX electronic universal material testing machine to evaluate the bending properties of the samples. The parameters of the AGX electronic universal material testing machine were set as follows: the loading speed of the bending strength test was 5 mm / min, and the loading speed of the bending modulus test was 1 mm / min;
[0135] Figure 3The mechanical properties result diagram of the prostate precursor matrix prepared by Examples 1-3 and Comparative Examples 1-3 is shown in the figure. As shown in the figure, the artificial prostate matrix prepared by Examples 1-3 has higher bending strength and bending modulus. The mechanical properties of Comparative Example 1 are the lowest, followed by Comparative Example 2. In the technical scheme described in Comparative Example 1, the polyetheretherketone fiber has not been modified, and the surface of the polyetheretherketone fiber has strong hydrophobic properties and poor compatibility with polyacrylate materials. It is easy to agglomerate in the process of preparing the artificial prostate matrix material, resulting in uneven dispersion of the polyetheretherketone fiber in the matrix material, resulting in a decrease in mechanical properties. The technical scheme described in Comparative Example 2 does not use DMAEMA-salt, Sulfonic acid groups usually have strong polarity and can produce strong hydrogen bonds with surrounding molecules, which helps to improve the polarity and stability of the polymer. In addition, sulfonic acid groups may also bring water solubility and enhance the cross-linking properties between material molecules. The introduction of DMAEMA salt not only enhances the density of the cross-linked network, but also changes the deformation mode of the material through the introduction of flexible structure, thereby improving the toughness of the prostate matrix material; Comparative Example 3 uses polyetheretherketone fiber material that has not been modified with polydopamine. Polydopamine has high adhesion and flexibility, and can effectively disperse stress under the action of external force and reduce the occurrence of brittle fracture, thereby improving the mechanical properties of the prostate matrix material.
[0136] Experimental Example 2
[0137] In this experimental example, the release performance of the artificial prostate tissue-induced composite material prepared in Example 1 and Comparative Examples 1-4 was measured. An artificial prostate matrix was prepared according to the sample size described in Experimental Example 1, and 5 mL of the cytokine coating precursor solution was coated on its surface. After photocuring, an artificial prostate tissue-induced composite material sample was obtained. The test was placed in a release bottle, 15 mL of PBS buffer was added, and the sample was placed on a shaker at 37°C and shaken at 120 rpm. The release liquid was aspirated every 12 hours, and then an equal amount of PBS buffer was added for replenishment. The obtained release was used to determine the BDNF content by ELISA analysis. The ELISA kit used was a brain-derived neurotrophic factor (BDNF) detection kit (Cloud-Clone (Beijing) Biotechnology Co., Ltd., item number SCA011Hu).
[0138] Figure 4The release performance result graph of the artificial prostate tissue-induced composite material BDNF prepared in Example 1 and Comparative Examples 1-4 is shown. As shown in the figure, the cytokine coatings prepared in Examples 1-4 of the present invention are in a stable state for the release of BDNF, the release amount of the coating prepared in Comparative Example 2 reaches 4564.1 pg / mL at the 72nd hour, and the release amount of Comparative Example 4 reaches 5326.5 pg / mL at the 48th hour, indicating that the coating disintegrates in the release liquid. It can be seen that the stability of the cytokine coatings of the artificial prostate tissue-induced composite materials prepared in Comparative Examples 2 and 3 is poor.
[0139] In this experimental example, the long-term release effect of the artificial prostate tissue-induced composite material of the prepared Example 1 and Comparative Examples 1 and 3 on the neural cell trophic factor was measured. An artificial prostate matrix was prepared according to the sample size described in Experimental Example 1, and 5 mL of the cytokine coating precursor solution was coated on its surface. After photocuring, an artificial prostate tissue-induced composite material sample was obtained. The test was placed in a release bottle, 15 mL of PBS buffer was added, and the sample was placed on a shaker at 37°C and shaken at 120 rpm. Samples were taken according to time points, and an equal amount of PBS buffer was added for supplementation. The obtained release was determined by ELISA analysis to determine the BDNF content, and the cumulative release rate (%) was calculated. The ELISA kit used was a brain-derived neurotrophic factor (BDNF) detection kit (Cloud-Clone (Beijing) Biotechnology Co., Ltd., item number SCA011Hu).
[0140] Figure 5 The long-term sustained release effect diagram of the artificial prostate tissue induced composite material prepared by Example 1 and Comparative Examples 1 and 3 of the present invention is shown in the figure. As shown in the figure, the artificial prostate tissue induced composite material prepared by Example 1 can achieve a BDNF release rate of 93.34% within 180 days, while Comparative Example 1 stops releasing between 60 days and 90 days, and Comparative Example 3 stops releasing between 90 days and 120 days. The reason for stopping the release of Comparative Examples 1 and 2 is that the cell coating falls off, resulting in a change in the structure of the artificial prostate induced composite material, so the release amount thereof is stopped from being measured; In Example 1, PEEK is used as the filling material. Since the PEEK fiber has poor dispersibility in acrylic resin and poor compatibility in aqueous environment, it is easy to cause separation from the acrylic resin, resulting in increased internal stress and unstable prostate matrix, which leads to the shedding of the coating. In Comparative Example 2, the compatibility of the PEEK fiber modified by peptide-metal is significantly improved. Due to long-term immersion in aqueous environment, and the peptide-metal and PEEK are only connected to each other by hydrogen bonding force, they are easily affected in the long-term action process.
[0141] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0142] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An artificial prostate tissue induction composite material, characterized in that: The composite material comprises an artificial prostate matrix and a cytokine coating; The artificial prostate matrix is obtained by curing the prostate matrix material, and the raw materials for preparing the artificial prostate matrix material include the following components in parts by weight: 5-10 parts of peptide-metal composite polyetheretherketone fiber, 12-15 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, and 20-25 parts of methyl methacrylate; The cytokine coating is formed by photocuring a cytokine coating precursor solution, and the raw materials for preparing the cytokine coating precursor solution include the following components in parts by weight: 5-8 parts of aldehyded chitosan powder, 14-18 parts of methacrylic anhydride, 3-5 parts of collagen powder, 0.8-1 parts of 2,4,6-trimethylbenzoyl-diphenyl oxide, and 5-6 parts of BDNF solution; The BDNF solution is a solution of BDNF dissolved in deionized water, with a mass concentration of 10 μg / mL; The preparation method of the peptide-metal composite polyetheretherketone fiber specifically comprises the following steps: T1, placing the polyetheretherketone fiber in a beaker, and washing it in an ultrasonic cleaning machine with acetone, anhydrous ethanol and deionized water in turn, the power of the ultrasonic cleaning machine is 500W, and the cleaning time is 30-60min, to remove impurities on the surface of the polyetheretherketone fiber, and after drying, obtain the pretreated polyetheretherketone fiber; T2, soaking the pretreated polyetheretherketone fiber prepared in step T1 in concentrated sulfuric acid, performing ultrasonic treatment at a power of 400-600 W for 3-5 min, filtering, washing the solid with acetone and deionized water in turn, and drying to obtain sulfonated polyetheretherketone fiber; T3, placing the sulfonated polyetheretherketone fiber prepared in step T2 in dichloromethane, adding aluminum chloride to mix, slowly adding succinic anhydride / dichloromethane solution, introducing nitrogen into the reaction system, raising the temperature to 40-45° C. under a nitrogen atmosphere, stirring at a speed of 150 rpm, reflux reaction for 4-6 hours, cooling the reaction system to room temperature, ultrasonically cleaning with sodium hydroxide solution, hydrochloric acid solution, deionized water and acetone at a power of 500 W, and drying to obtain modified polyetheretherketone fiber; T4, dispersing the modified polyetheretherketone fiber prepared in step T3 in DMF, adding zinc chloride and mixing evenly, adding dopamine solution, stirring at a speed of 300-3500 rpm, adding p-toluenesulfonic acid, raising the reaction temperature to 90-100°C, stirring and reacting for 4-6 hours, removing the solvent by reduced pressure distillation, preparing a Tris buffer solution with a pH of 8.5-9.0, adding it to the reaction system, placing it at 37°C, stirring and reacting at a speed of 500-600 rpm for 20-28 hours, filtering, washing the precipitate with deionized water, anhydrous ethanol and acetone, and vacuum drying to obtain polydopamine-modified polyetheretherketone fiber; T5. Dissolve L-histidine in tetrahydrofuran, add triphosgene under nitrogen atmosphere, raise the reaction temperature to 50-60°C, stir and react for 1-2h, wait for the reaction system to cool, add n-hexane for sedimentation, filter, take the precipitate, recrystallize with ethyl acetate, and dry to obtain histidine-NCA; T6, placing the polydopamine-modified polyetheretherketone fiber prepared in step T4 in dichloromethane, adding the histidine-NCA prepared in step T5, placing it in an argon atmosphere, stirring at a speed of 400-600 rpm for reaction, after 24-36 hours, filtering to remove the solvent, washing with DMF and dichloromethane, and vacuum drying to obtain a polypeptide composite polyetheretherketone fiber; T7. Disperse the polypeptide composite polyetheretherketone fiber prepared in step T6 in anhydrous ethanol, add zinc chloride, stir at 400-500 rpm at room temperature, react for 4-6 hours, dialyze with Tris buffer using a 3500Da dialysis bag for 24 hours, and freeze-dry to obtain the peptide-metal composite polyetheretherketone fiber.
2. The artificial prostate tissue induction composite material according to claim 1, characterized in that: The artificial prostate tissue induction composite material also includes a signal acquisition module, a signal control module and a treatment module.
3. The artificial prostate tissue induction composite material according to claim 2, characterized in that: The signal acquisition module collects the bladder and urethra pressure status, urine outflow and overflow status, and sends the data to the signal control module; the signal control module controls the treatment module to perform continuous discharge stimulation to regulate the bladder and urethra sensation and relieve the condition of frequent urination and urinary incontinence.
4. The method for preparing an artificial prostate tissue induction composite material according to any one of claims 1 to 3, characterized in that: The specific steps include: S1. Place the peptide-metal composite polyetheretherketone fiber in an ethanol solution, stir at a speed of 200-250rpm, and fully disperse for 1-2h, then add DMAEMA-salt and methyl methacrylate to the reaction system, continue stirring and reacting for 2-3h, and then perform reduced pressure distillation to remove ethanol and deionized water to obtain an artificial prostate matrix solution; the mass concentration of the modified polyetheretherketone fiber in the ethanol solution is 10-25g / L; S2, adding the artificial prostate matrix solution prepared in step S1 to the sodium persulfate solution, adjusting the pH to 8.5, and after mixing evenly, transferring to the prostate matrix mold, raising the reaction temperature to 40-50° C., and curing for 3-5 hours, demoulding after curing, washing with deionized water, and vacuum drying to obtain an artificial prostate matrix; the mass fraction of sodium persulfate in the sodium persulfate solution is 10%-20%, and the added volume of the sodium persulfate solution is 0.5%-1% of the volume of the artificial prostate matrix solution; S3. Apply the cytokine coating precursor solution to the inner and outer surfaces of the artificial prostate precursor prepared in step S2, and irradiate under blue-violet light for 30-60s. After the cytokine coating is cured, an artificial prostate tissue induction composite material is obtained.
5. The method for preparing the artificial prostate tissue induction composite material according to claim 4, characterized in that: In step T3, the mass concentration of the sulfonated polyetheretherketone fiber in dichloromethane is 25-50 g / L; the mass concentration of succinic anhydride in dichloromethane is 0.065-0.1 g / mL, the mass ratio between the sulfonated polyetheretherketone fiber and succinic anhydride is 2:1.5-2.5; the mass ratio between the sulfonated polyetheretherketone fiber and anhydrous aluminum chloride is 1:1-1.2; In step T4, the mass concentration of the modified polyetheretherketone fiber in DMF is 10-15 g / L; the amount of zinc chloride added is 10%-20% of the mass of the modified polyetheretherketone fiber; the dopamine solution is a solution of dopamine dissolved in an ethanol aqueous solution, and the mass concentration of dopamine in the ethanol aqueous solution is 40-60 g / L; the mass ratio between dopamine and the modified polyetheretherketone fiber is 1:0.7-0.9; in step T4, the mass of p-toluenesulfonic acid added is 1%-2% of the mass of the modified polyetheretherketone fiber; the volume ratio of the added volume of the Tris buffer solution to the DMF solvent is 1-1.5:
1.
6. The method for preparing the artificial prostate tissue induction composite material according to claim 5, characterized in that: In step T5, the mass concentration of L-histidine in tetrahydrofuran is 60-80 g / L; the mass ratio of L-histidine to triphosgene is 1:1.2-1.5; In step T6, the mass concentration of the polydopamine-modified polyetheretherketone fiber in dichloromethane is 40-50 g / L; the mass ratio between the polydopamine-modified polyetheretherketone fiber and histidine-NCA is 1:3-4; In step T7, the mass concentration of the polypeptide composite polyetheretherketone fiber in anhydrous ethanol is 10-15 g / L; the added mass of the zinc chloride is 15%-20% of the mass of the polypeptide composite polyetheretherketone fiber.
7. The method for preparing the artificial prostate tissue induction composite material according to claim 6, characterized in that: The method for preparing the cytokine coating precursor solution specifically comprises the following steps: K1. Place chitosan in deionized water, adjust the pH to 5.5-6.5 to completely dissolve the chitosan, add sodium periodate, mix well, place at room temperature, react in the dark for 6-8 hours, add ascorbic acid to terminate the reaction until the color of the reaction system no longer changes, and after the reaction is completed, freeze-dry to obtain aldehyded chitosan; K2, dispersing the aldehyde-modified chitosan prepared in step K1 in DMF solvent, adding hydrogen peroxide, wherein the volume ratio of the added hydrogen peroxide to the volume of the DMF solvent is 1-1.5:1, stirring at a speed of 150 rpm until the aldehyde-modified chitosan is completely dissolved, adding methacrylic anhydride, adjusting the pH of the reaction system to 8-9, placing in an ice-water bath environment, continuing to stir and react for 12 hours, placing in a dialysis bag after the reaction is completed, dialyzing with deionized water for 2 days, and freeze-drying to obtain modified chitosan powder; K3. Dissolve collagen in a NaCl aqueous solution, add the modified chitosan powder prepared in step K2, stir the reaction at a speed of 200 rpm, add 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, mix evenly at 4°C, add BDNF solution, continue stirring for 2-3 hours, and obtain a cytokine coating precursor solution.
8. The method for preparing the artificial prostate tissue induction composite material according to claim 7, characterized in that: In step K1, the mass concentration of chitosan in deionized water is 15-25 g / L; the mass ratio of chitosan to sodium periodate is 10:8-9.
9. The method for preparing the artificial prostate tissue induction composite material according to claim 8, characterized in that: In step K2, the mass concentration of the aldehyde-modified chitosan in the DMF solvent is 40-60 g / L; in step K3, the mass fraction of the NaCl aqueous solution is 1%-1.2%; and the mass concentration of the collagen in the NaCl aqueous solution is 20-25 g / L.
Citation Information
Patent Citations
Skull repair polyether-ether-ketone material and preparation method thereof
CN114452441A
Bio-functionalized porous polyether-ether-ketone bone tissue scaffold material and preparation method thereof
CN117427212A